A Corpus Study of Brexit Political Discourse: Exploring Modality through Lexical Modals - Encarnación Almazán Ruiz; Aroa Orrequia-Barea (Miscelánea: A Journal of English and American Studies)
This paper aims to analyse the lexical modals used in the political speeches given by Boris Johnson and Jeremy Corbyn during the final months of the Brexit process. This study explores whether lexical choice shows the politicians’ commitment to their constituents, particularly to determine which lexical modals each politician uses and which semantic implication(s) these modals convey. The study is descriptive-interpretative and uses the corpus-assisted discourse studies approach. It contributes to research on modality in the English language by examining parts of speech other than (semi)auxiliary modal verbs. As the corpus analysis shows, lexical modals are a prominent resource employed by politicians to present facts to their audience.